Experimental assessment of stiffness and energy dissipation properties of disk-shaped polymer-based composite specimens by in-plane torsion testing. (March 2020) - Cosco, Francesco; Serratore, Giuseppe; Catera, Piervincenzo Giovanni; Gagliardi, Francesco; Luberto, Eduardo; Mundo, Domenico
Abstract: Torsion testing machines are widely used either to measure the strength, stiffness and stress-strain properties of materials or to replicate real-life service conditions. In this paper, a novel experimental method is presented, based on the development of a dedicated steel structure to be used in conjunction with a universal testing machine. This equipment allows applying cyclic in-plane torsion loads on disk-shaped components. The proposed approach aims to enable the assessment of stiffness and damping properties on specimens enabling the application of higher loads in comparison with the traditional machines. Specifically, dynamic trials were performed by attaching the composite specimens and the steel structure to the testing machine, such that the uniaxial controlled displacements can be used to exert the desired cyclic loads onto the specimen. Both torsional stiffness and energy loss were measured from the steady-state load-displacement hysteresis cycles. Amplitudes of sine signals, from 0.05 to 0.2 mm, and a frequency ranging between 1 and 20 Hz, were used in the experiments. The results are presented comparing the behaviour of two polymer matrix composites, with the same number of identical laminae, but characterized by different stacking sequences, namely unidirectional and quasi-isotropic configurations. Highlights: A novel approach was proposed to exert cyclic in-plane torsion loads on composites. The loads were provided by combining a testing machine and a dedicated structure. The approach enables the assessment of material stiffness and damping properties. Sine signals were used to assess high frequency and amplitude dependencies. The approach was tested quantifying the dynamic behaviour of different laminate layups.